Theta, Phi and Pi on the Stage of the World Theatre - Zuzana Svobodová (Theology and Philosophy of Education, 2023)
It is the editorial for the first issue of the second volume of the journal Theology and Philosophy of Education. The journal’s logo is described and interpreted here in the context of the journal’s aim. All the texts of the offered issue are briefly introduced here.